A History of the Early Islamic Law of Property : Reconstructing the Legal Development, 7th-9th Centuries - Yanagihashi, Hiroyuki (Brill Book Archive Part 1, ISBN: 9789004472495., 2004)
The present book is devoted to an analysis of positive solutions concerning matters related to civil liability, certain kinds of sale that would evolve into agency and some forms of partnership, and the prohibition of ribā. The analysis has two aims. First, it attempts to trace the process by which some hitherto unclarified institutions and transactions were elaborated to form an integral part of the classical Islamic law of property. The second aim to determine how and why the teachings of particular jurists became predominant in Iraq and Medina and laid the foundation of the Ḥanafī and the Mālikī schools of law in each respective region.